New Media, Pandemic, and Discourse on Religious Moderation: A Study of NU and Muhammadiyah Websites - Adeni, Adeni; Hasanah, Silviatul (UIN Sunan Kalijaga Yogyakarta, 2023)
The websites of NU and Muhammadiyah effectively reconcile religious beliefs with the practicalities of government policies during the pandemic. These organizations have crafted legal frameworks that streamline religious rituals amidst COVID-19 restrictions and containment measures. This study explores how their discourse promotes a harmonious fusion of religious and state values, particularly within organizations known for their moderate approach to religious matters. Utilizing discursive practice and discourse analysis, the study reveals that both NU and Muhammadiyah establish pandemic-specific worship guidelines aligned with government policies. While NU's approach relies on classical Fiqh arguments, Muhammadiyah adopts a more pragmatic and progressive stance. Nevertheless, both organizations share the common goal of ensuring ease and accessibility for the public to practice their faith during these challenging times. This facilitation, grounded in sound reasoning, incorporates adaptations to state policies when selecting thematic approaches. This alignment highlights that NU and Muhammadiyah's moderation concept not only considers the applicability of religious texts to local circumstances but also supports government initiatives aimed at public welfare and addressing the COVID-19 crisis.